Ornamental Palms for Central Florida - Timothy K. Broschat; James E. Davis (EDIS)
Palms are often thought of as symbols of the tropics, but fortunately there are a number of palm species that grow in warm, temperate climates, such as that of Central Florida. This 8-page fact sheet was written by Timothy K. Broschat and James E. Davis, and published by the UF Department of Environmental Horticulture, January 2013.